Pengaruh Kedisiplinan Kerja dan Kompetensi Terhadap Kinerja Karyawan pada PT. Skinsol Kosmetik Industri Kabupaten Bandung Barat - Yudiyanto Joko Purnomo; Riski Amalia Fadhilla (Lembaga Pengembangan Kinerja Dosen, 2024)
This research can be concluded as follows. The method used in this research is a quantitative method. The population in this study was 39 permanent employee respondents. This research uses the census method and uses a questionnaire for data collection. The results of validity and reliability tests using the Person product moment correlation method and Cronbach's alpha, it is known that the items created are valid and calculations show that work discipline partially has a significant positive effect on employee performance, while partial competence has a significant positive effect on employee performance. The results of calculating the value of the influence of work discipline and competence simultaneously by looking for the coefficient of determination show how much influence there is between the two variables which can be studied from the R value and is 0.742. The size of the R square (R2) is 0.551, so the coefficient of determination (KD) is 0.551 x 100% = 55.1%, this means that it shows the influence of work discipline and competence on employee performance by 55.1% while the remaining 44.9% is influenced by other variables.